Tay Sachs disease variant B1: iPSC and NGS as the basis for a cellular model - Ribeiro, Diogo (2022)
Tay Sachs disease variant B1 (TSD B1; OMIM 272800) is a neurodegenerative lysosomal storage disease (LSD) which, although rare, is the most frequent form of TSD in Portugal. The mutation p.R178H (c.533G>A; rs28941770), associated with TSD B1, leads to a mutant HexA protein with altered kinetics and reduced residual activity. The availability of disease-relevant cell types derived from induced pluripotent stem cells (iPSCs) provides a model for studying the pathogenic mechanisms and, eventually, test therapeutic approaches for TSD B1 patients. The main objectives of this project is, by using iPSCs, to generate a neuronal TSD B1 specific cellular model and to implement the genetic profiling by Next Generation Sequencing (NGS) to examine potential changes in the manipulated cells. In the present work, the iPSC reprogramming and differentiation into neural progenitor cells (NPCs) is presented, as well as the NGS results from the donor cells. As a first step, iPSCs from a control fibroblast cell line and from TSD B1 fibroblasts were obtained by using a non-integrative approach with episomal vectors, the control was further differentiated into NPCs. When generating iPSCs it is important to have multiple characterisation steps. The iPSCs have to mimic the donor background at genetic and protein levels. Furthermore, iPSCs or iPSC-derived lines need to be free of the reprogramming and differentiation markers while presenting specific cell-type markers. The frailty of these cells and adverse conditions (first lockdowns and later accidental deprivation of liquid nitrogen) led to the interruption of the iPSC work. In the meantime, we did a lysosomal-related gene profiling of the DNA from the original cell lines. By using an in-house customized NGS panel, we obtained results of the cells in a “naïve” state to later compare with TSD B1 iPSCs and NPCs obtained from control iPSCs. The results presented consist of the preliminary work to obtain a cell model of TS-B1.